2009
DOI: 10.1016/j.jtcvs.2008.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Regional wall motion abnormalities and scarring in severe functional ischemic mitral regurgitation: A pilot cardiovascular magnetic resonance imaging study

Abstract: In a pilot study of cardiovascular magnetic resonance imaging in severe functional ischemic mitral regurgitation, severity of posterior papillary muscle region scarring correlated with decreased segmental wall motion and mitral regurgitation early after coronary revascularization and annuloplasty. Routinely assessing scar burden may identify patients for whom annuloplasty alone is insufficient to eliminate mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 22 publications
1
27
0
2
Order By: Relevance
“…Many previous studies reported that patients undergoing surgery before developing contractile dysfunction and dilatation had better postoperative clinical outcomes in the short and long term than those with contractile deficiencies [[6], [9]]. Several techniques including magnetic resonance [10], deformation imaging [11] and biomarkers, such as brain natriuretic peptide [4], have been used for the early detection of contractile dysfunction. We hypothesized that the serum OPN level may be helpful in determining the timing of mitral valve surgery and may serve as a predictor of postoperative EF impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies reported that patients undergoing surgery before developing contractile dysfunction and dilatation had better postoperative clinical outcomes in the short and long term than those with contractile deficiencies [[6], [9]]. Several techniques including magnetic resonance [10], deformation imaging [11] and biomarkers, such as brain natriuretic peptide [4], have been used for the early detection of contractile dysfunction. We hypothesized that the serum OPN level may be helpful in determining the timing of mitral valve surgery and may serve as a predictor of postoperative EF impairment.…”
Section: Discussionmentioning
confidence: 99%
“…90,91 Therefore, CMR offers the potential to directly quantify RgV, RgF, and ROA in patients with MR. Because of its accuracy and precision in measuring LV volumes, CMR is useful for evaluation of LV remodeling in MR. 92 Finally, CMR can identify the presence of scar or fibrosis using delayed hyperenhancement of gadolinium contrast agents, a finding that may be particular relevant in FMR. 93,94 Limitations of CMR include cardiac arrhythmias that preclude adequate gating, pacemakers or implantable cardioverter-defibrillators, and claustrophobia. Direct measurement of ROA by CMR may be limited by slice thickness (typically 5 mm) and cardiac translation, which may render it difficult to align the image precisely with the narrowest part of the VCA.…”
Section: Role Of Exercise Testingmentioning
confidence: 99%
“…Flynn et al recently reported the importance of papillary muscle scar burden to identify patients for whom annuloplasty alone is insufficient to prevent recurrent regurgitation. 29 Further investigation such as 3-dimensional analyses might be more informative to determine whether the precise amount or location of hyperenhancement tissue predicts adverse outcomes.…”
Section: Study Limitationsmentioning
confidence: 99%